PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS TERHADAP BELANJA DAERAH PEMERINTAH KABUPATEN MUSI BANYUASIN - Siti Rohana; Rano Asoka (Surplus: Jurnal Riset Mahasiswa Ekonomi, Manajemen, dan Akuntansi, 2021)
This study aimed to determine the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) on the Regional Expenditure of the Government of Musi Banyuasin Regency. The types and sources of data used by the author in this study were secondary data. In this study, the author used quantitative analysis techniques. The quantitative analysis technique used by the author in this study was by testing the hypothesis. This test was used to determine whether the independent variable significantly influences the dependent variable. The results of the study stated that based on the F test it could be concluded that the regional own-source revenue, general allocation funds and special allocation funds together had an influence on regional expenditure. This was because the calculated F value of 6.758> from the F value of the table 6.608 and based on the t test it could be concluded that the original regional revenue, general allocation funds and special allocation funds partially had an influence on regional spending. This was because the value of t arithmetic local revenue to regional expenditures amounted to 5.204, general allocation funds to regional expenditures amounted to 2.951 and special allocation funds to regional expenditures amounted to 2.968 greater than t table that amounted to 2.105.